Menopausal hormone therapy and risk of colorectal cancer in the European Prospective Investigation into Cancer and Nutrition. - Tsilidis, K; Allen, N; Key, T; Sanjoaquin, M; Bakken, K; Berrino, F; Fournier, A; Lund, E; Overvad, K; Olsen, A; Tjønneland, A; Byrnes, G; et al. (2011)
Menopausal hormone therapy (HT) may influence colorectal cancer risk. A total of 136,275 postmenopausal women from the European Prospective Investigation into Cancer and Nutrition were followed for an average of 9 years, during which time 1,186 colorectal cancers were diagnosed. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox proportional hazards models stratified by center and age, and adjusted for body mass index, smoking, diabetes, physical activity and alcohol consumption. Compared to never use of HT at study enrollment, current use of estrogen-only (HR, 1.02; 95% CI, 0.79-1.31) or estrogen plus progestin (HR, 0.94; 95% CI, 0.77-1.14) was not significantly associated with the risk of colorectal cancer, and these associations did not vary by recency, duration, route of administration, regimen or specific constituent of HT. Our results show no significant association of estrogen-only or estrogen plus progestin therapy with colorectal cancer risk.